A 3-D net based on weak metallophilic (Cu⋯Cu) interactions. Issue 28 (30th June 2016) - Zhou, Jian; Tan, Xiaofeng; Hu, Feilong; Zou, Hua-Hong; Almeida Paz, Filipe A.; Fu, Lianshe; Zhao, Rongqing
Abstract : The interconnection of 1-D [Cu(IN)] chains via weak metallophilic (Cu⋯Cu) interactions gives a 3-D network with photocatalytic properties. Abstract : A novel 3-D binary copper(i ) polymer [Cu(IN)] n (1, IN = isonicotinate) has been solvothermally synthesized. 1-D [Cu(IN)] chains of1 are interconnected by weak metallophilic (Cu⋯Cu) interactions to form a 3-D net. The theoretical band structure and photocatalytic and fluorescence properties have also been studied.